Discoloration of resin based composites in natural juices and energy drinks - Antonov, Milica; Lenhardt, Lea; Manojlović, Dragica; Milićević, Bojana; Dramićanin, Miroslav D. (Vojnosanitetski pregled, 2020)
Background/Aim. Discoloration of dental restorations makes them aesthetically unacceptable and is a frequent reason for replacement of composite restorations. The aim of this study was to evaluate changes of color and fluorescence of resin-based composites (RBCs) exposed to natural juices and energy drinks. Methods. Microhybrid composite Gradia DirectTM Extra Bleach White disc-shaped specimens (n = 35) were immersed in three different natural juices and four different energy drinks. Absorption spectra of natural juices and energy drinks, diffuse reflection and fluorescence of composite samples were measured prior and after seven- day immersion by spectrophotometer Thermo Evolution 600 and spectrofluorometer Fluorolog-3-221. Composite’s color was calculated from diffuse reflection spectra and expressed in CIELAB color space (Commission International de l’Eclairage). Results. All natural juices and energy drinks induced color change of resin based composites, but to the different extent. Only aronia and carrot juices induced total color change considerably higher than clinically acceptable threshold, 9.3 and 6.2, respectively. All energy drinks and aronia juice induced notable decrease in fluorescence; the highest change of 28% was evidenced in the case of aronia juice. Conclusion. Change of color and fluorescence will appear differently with various solutions due to different chemical composition and concentration of colorant species in different beverages. Solutions with higher optical absorption induced higher total color change. Discoloration of composites in aronia and carrot juices is similar to those earlier reported for red wine, tea and coffee.
Keywords: dental materials; composite resins; materials testing; color; energy drinks; fruit and vegetable juices; fluorescence.